2018
DOI: 10.1021/acssuschemeng.8b03180
|View full text |Cite
|
Sign up to set email alerts
|

Metal Acetylacetonates as a Source of Metals for Aqueous Synthesis of Metal–Organic Frameworks

Abstract: Demand continues for environmentally sound, high-yielding processes for the large-scale production of metal-organic frameworks (MOFs). Here we describe the use of metal acetylacetonate complexes as an alternative source of metals for the aqueous synthesis of MOFs. We have synthesized several carboxylate-based Zr(IV)-(UiO-66-NH2, Zr-fumarate, UiO-66-(OH)2, UiO-66-COOH and UiO-66-(COOH)2), Fe(III)-(MIL-88A) and Al(III)-(CAU-10) porous MOFs from their corresponding metal acetylacetonates in good yields (typically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…As shown in Figure 2 b‐c, PXRD patterns evidenced that highly crystalline UiO‐66‐NH 2 , UiO‐66‐COOH ( fcu topology, see structure in Figure 1 c) and DUT‐67(PDA) ( reo topology, see structure in Figure 1 d) were synthesized successfully following a similar synthesis protocol. Notably, synthesizing the functionalized UiO‐66‐COOH at room temperature is not straightforward due to the lower p K a of trimellitic acid in comparison to other derivatives (e.g.‐NH 2 , ‐H) that usually favors the formation of amorphous compounds [8b, 13c] . The room‐temperature obtained MOFs presented higher surface areas (UiO‐66‐NH 2 (1255(±5) m 2 g −1 ), UiO‐66‐COOH (1050(±6) m 2 g −1 ) and DUT‐67(PDA) (1020(±6) m 2 g −1 )) than the theoretical values (see Figure 2 e,f), in agreement with the presence of defects, as mentioned above for MOF‐801 (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 2 b‐c, PXRD patterns evidenced that highly crystalline UiO‐66‐NH 2 , UiO‐66‐COOH ( fcu topology, see structure in Figure 1 c) and DUT‐67(PDA) ( reo topology, see structure in Figure 1 d) were synthesized successfully following a similar synthesis protocol. Notably, synthesizing the functionalized UiO‐66‐COOH at room temperature is not straightforward due to the lower p K a of trimellitic acid in comparison to other derivatives (e.g.‐NH 2 , ‐H) that usually favors the formation of amorphous compounds [8b, 13c] . The room‐temperature obtained MOFs presented higher surface areas (UiO‐66‐NH 2 (1255(±5) m 2 g −1 ), UiO‐66‐COOH (1050(±6) m 2 g −1 ) and DUT‐67(PDA) (1020(±6) m 2 g −1 )) than the theoretical values (see Figure 2 e,f), in agreement with the presence of defects, as mentioned above for MOF‐801 (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Few recent reports describe one‐step RT synthetic approaches of UiO‐type MOFs [8b, 16] . However, they rely on specific reactants or additives to promote nucleation, associated to cost issues and/or to the presence of impurities in the resulting products.…”
Section: Introductionmentioning
confidence: 99%
“…Some organic zirconium salts, such as n‐propanol zirconium (Zr(OnPr) 4 ) [29] and zirconium acetylacetonate (Zr(acac) 4 ), [30] can avoid the generation of corrosive by‐products in the synthesis process and yield high quality UiO‐66 crystals, thus, can also be viewed as recommended green metal sources. By using Zr(OnPr) 4 as metal source, series of Zr−MOFs can be synthesized at mild condition, even room temperature [29a] .…”
Section: Green Raw Materialsmentioning
confidence: 99%
“…For example, Sánchez-Sánchez et al [174] reported the waterbased synthesis of a number of MOFs at room temperature by employing organic salts as anionic building blocks, including MOF-5, MOF-74, MIL-100(Fe) and MIL-53-Al-X (X = H, NH 2 , NO 2 ). Similarly, Avci-Camur et al [175] have described the water-based synthesis of two types of MOFs (Zr-MOFs and MIL MOFs) using metal acetylacetonate complexes as alternative source of metals. Most recently, Jacobsen et al [176] reported the successful water-based syntheses of a series of Ce (IV) -MOFs (UiO-66, CAU-41 and CAU-44) with three different topologies (fcu, body-centered cubic (bcu), and body-centered tetragonal (bct)) within 30 min via microwave-assisted reactions using six chiral and achiral alkane dicarboxylic C 4 -acids as ligands.…”
Section: Pcn Seriesmentioning
confidence: 99%